2011
DOI: 10.1021/jp207521w
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer and Trapping in Natural p–n Bipolar Polymer-Based Bilayer Films

Abstract: Cyclic voltammetry and spectroelectrochemistry were separately employed to study and observe the electron transfer and trapping behavior between two bipolar polymers synthesized by the cyclic voltammetry method. The poly(DNTD) and poly(Cl 4 DPTD) were pair-sequentially electropolymerized on a Pt disk electrode and indium tin oxide (ITO) transparent electrodes for electrontransfer and electron trapping studies, respectively. Interestingly, the electrochemical responses of the bilayers at negative potentials vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Peaks from DPV at 0.47 V and 1.01 V, together with oxidation peaks by CV at around 0.50 V and 1.10 V for compound 1 suggest the formation of diphenylbenzidene after two subsequent 1 e oxidation reactions. E 1/2 values at −0.50 V and −1.00 V were consistent with DPV peaks appearing at −0.55 V and −1.02 V for the two 1 e reductions of the NDI core (Figure 8) [34,35,37,38]. Similarly, two 1 e reductions of the 4,4′-biphthalic core in 3 were observed at potentials of −1.27 V and −1.17 V by DPV, which were consistent with E 1/2 values at −1.33 V and −1.14 V by CV.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Peaks from DPV at 0.47 V and 1.01 V, together with oxidation peaks by CV at around 0.50 V and 1.10 V for compound 1 suggest the formation of diphenylbenzidene after two subsequent 1 e oxidation reactions. E 1/2 values at −0.50 V and −1.00 V were consistent with DPV peaks appearing at −0.55 V and −1.02 V for the two 1 e reductions of the NDI core (Figure 8) [34,35,37,38]. Similarly, two 1 e reductions of the 4,4′-biphthalic core in 3 were observed at potentials of −1.27 V and −1.17 V by DPV, which were consistent with E 1/2 values at −1.33 V and −1.14 V by CV.…”
Section: Resultssupporting
confidence: 63%
“…N, N′-bis[ p -phenylamino(phenyl)]-1,4,5,8-naphthalenetetracarboxylic diimide (DNTD) and N, N′-bis[ p -phenylamino(phenyl)]-3,4,9,10-perylenetetracarboxylic diimide (DPTD) were reported by Cammarata [34,35,36] and Guo [37,38,39], respectively. Single crystal structures provide rich information about packing and weak interactions, including hydrogen bonds, π–π stacking, and the van der Waals force.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of p-type and n-type polymers can be formed by layering the two different polymers on top of each other, forming a bilayer device. For instance, Lantonen et al solution-casted n-type poly­(benzimidazobenzophenanthroline)–poly­(ethylene oxide) (BBL–PEO) on p-type polyazulene (PAz) to form p-type/n-type composite layers. The composite showed formation of both p-type and n-type charge carriers, where p-type doping was dominated by PAz and n-type doping was dominated by BBL–PEO.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the structure of the catalysts may have an inuence on the catalytic performance. 26,27 Chae et al 2 focused their study on the structure of ordered mesoporous silica supports. Along with research thorough, zirconia was later reported as a successful replacement for tantalum oxide.…”
Section: Introductionmentioning
confidence: 99%